Четвертинна мегафауна у колекціях Чернівецького університету - Рідуш, Богдан; Поп'юк, Яна; Костюк, Уляна; Шкеул, Марія (My University, 2023)
The Quaternary megafauna remains are unequally represented in a few collections of the University of Chernivtsi. They started during the Austrian period, continued in the Romanian period (1918-1944), and were significantly extended in the 2000s. They contain a few thousand bones, mainly from the Late Pleistocene and late Middle Pleistocene, rarely from Pliocene and Early Pleistocene. The bone material was used in several international scientific publications, including paleozoological morphology, paleo-DNA, isotopic compound, paleobiogeography, and archaeozoology.
Quaternary megafauna in the collections of Chernivtsi University